Body Segment Parameters During GS Turn in Recreational Skiers - Mijo Curic; Edin Mujanović; Tarik Huremović; Amra Nožinović Mujanović (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2017)
Study aim was to analyze the kinematic parameters of the body of the examinees, without competitive experience in skiing, in order to determine the competitive efficiency. The participants in this research were 23 male students from the Faculty of physical education and sport, aged 22±6 months, who attended the classes in the subject alpine skiing. Examinees were divided into two categories, according to duration of the course run, in order to determine whether there is the differences in body segment parameters during giant slalom turn. Using Independent Samples t-test we see that the examinees differ on a statistically significant level in variables duration of the turn p=0.000, duration of the course run p=0.000 and inclination of the body p=0.030, and that the differences are in favor of faster examinees. The analysis of the results in this research has shown that there is a relation between the measured body segment parameters and duration of the course run, or that the technique of skiing has a direct impact on the competition in alpine skiing.